Effect of diverse low energy-dense versus healthy diet on metabolic outcomes in overweight/obese adolescents: a randomized controlled trial - Aghaei, Niloofar; Rouhani, Mohammad Hossein; Tabatabaei, Fatemeh; Larijani, Bagher; Azadbakht, Leila (Progress in Nutrition, 2019)
Background: Dyslipidemia and impaired glucose metabolism are prevalent among overweight/obese adolescents. Although several dietary interventions used to reduce these complications, no study has been conducted regarding the effect of a diverse low energy-dense diet (DLED) on metabolic outcomes. Objective: To assess the effect of diverse low energy-dense diet on anthropometric variables, lipid profile and fasting blood sugar in overweight/obese adolescents aged 8-18 years. Methods: For this parallel clinical trial, 40 overweight/obese adolescents were randomly assigned to a DLED or a healthy recommendation based diet for 10 weeks. Physical activity and dietary intakes were recorded during the study. Total energy expenditure was estimated by Harris Benedict equations for each subject. To reduce energy density, a low-fat (25% fat, 15% protein and 60% carbohydrate) diet rich in dietary fiber and water was prescribed. The dietary variety was increased by recommending adolescents to consume at least one-half of subgroups of each main food group daily. Healthy nutritional recommendations were focused on limiting fast foods, fatty foods, added sugar, sugar sweetened beverages, French fries and unhealthy fat intake. Also, these recommendations encourage adolescents to consume more fruits and vegetables, whole grains, low-fat diary and water. Total cholesterol, low density lipoprotein, high density lipoprotein, triglyceride, fasting blood sugar and anthropometric variables were assessed at baseline and end-point. Results: The data of 40 adolescents were analyzed. Within groups analysis showed that there was a significant reduction in triglyceride (p=0.04) and low density lipoprotein (p<0.01) in DLED group. We could not find any significant difference in baseline relative to endpoint measurements in both groups. Changes of anthropometric and biochemical variables were compared in a crude and adjusted models. We could not find any significant changes in anthropometric and biochemical variables between two diet groups. Conclusion: This study showed that compliance to a DLED diet may result in a significant decrease in TG and LDL after 10 weeks. However, we did not observe any significant difference in changes of variables between members of DLED group and those who consumed a healthy diet.